Back to the Family: Rethinking the Role of Parents in Schooling (Сase of the Republic of Guinea) - Katerina V. Fofanova; Adama Conde (Интеграция образования)
Introduction. The problem of the interaction between family and school is being actively discussed in a number of African countries in the context of the active reform of the education sector. On the one hand, the educational system is being modernized; on the other hand, the potential of traditional education remains, emphasizing the special role of the family in the formation of fundamental values as the main vector of modern educational reform in Africa. The purpose of this article is to identify the role of the family in the education of schoolchildren and the development of education in Guinea, based on an expert survey.